Copper–zinc alloy electrodeposition mediated by triethanolamine as a complexing additive and chemical dealloying. (1st October 2019) - Vivegnis, S.; Delhalle, J.; Mekhalif, Z.; Renner, F.U.
Abstract: Nanoporous metals offer an open nanostructured network with a very high specific area and nanoporous templates can be used in many applications from energy storage and catalysis to sensors. One way to produce nanoporous (noble) metal templates is the dealloying approach starting from an alloy based on elements of different reactivities. In this work, co-electrodeposition of CuZn alloys is performed with triethanolamine (TEA) as a complexing agent to produce CuZn precursor films for further dealloying. To investigate the phenomena of electrodeposition, the electrochemical behavior of a copper substrate is compared to an ITO substrate in different NaOH electrolytes, with and without metal salt or additive. Cyclic voltammetry shows that a passivating layer forms on a copper substrate but is of lower stability in the presence of TEA. Potentiostatic electrodeposition from copper sulfate and zinc sulfate with TEA leads to Zn-rich γ-brass coatings. Nanoporous structuration is obtained after chemical dealloying of the electrodeposited alloy coatings. The dealloying process induces an increase of the electrochemically active surface area by a factor 25. The nanoscale structuration is confirmed by FIB-SEM. Graphical abstract: Image 1 Highlights: Formation of nanoporous copper from electrodeposited Zn-rich CuZn alloy precursors. Increase of the electrochemically active surface area of coating by a factor of 25. Triethanolamine additive induces the passive layer dissolution formed on copper substrate in basic conditions. Promising material for energy storage as well as biosensors and catalysis applications.